$$$... Jumping Out for Steelband' - Blackman, D Anthony (Guardian)
While T and T Carnival is seen as a lucrative venture, this year's investment in steelbands has garnered the inevitable negative aura and lack of respect which surrounds the steelband movement, and by extension the national instrument. The Starlift Steel Orchestra, however, remains as one of the successful, though struggling survivors of the cultural holocaust.
Keywords: Steel band music -- Trinidad and Tobago; Carnival -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Panorama (Musical festival)